Endlessly Signifying What Is Absent - Jean Frémon (Studies in 20th & 21st Century Literature, 1987)
Endlessly Signifying What Is Absent
Keywords: Jean Frémon; signs; sound; meaning word; maxims; essay; Ainsi toujours designant ce qui manque